1997
DOI: 10.1017/s1352465800018397
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Problem-Solving and Autobiographical Memory in Parasuicide Patients

Abstract: The relationship between effectiveness of interpersonal problem-solving and specificity of autobiographical memory was examined for 35 patients admitted to an inner-city District General Hospital following a deliberate drug-overdose. The results replicated those of Evans, Williams, O'Loughlin and Howells (1992) in finding a significant correlation between ineffective problem-solving and the over-general retrieval of autobiographical memories, giving further support to the suggestion that an over-general memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 22 publications
5
43
0
Order By: Relevance
“…For instance, in clinical depression, a sustained orientation toward the retrieval of general or categoric memories (Williams & Dritschel, 1992) may make it increasingly difficult to retrieve specific episodes or details, further compounding the impairments in problem solving that overly general memory retrieval may yield (e.g., Raes et al, 2005;Sidley, Whitaker, Calam, & Wells, 1997;see, especially, Watkins, Teasdale, & Williams, 2000, for evidence that alterations of cognitive state at the time of memory retrieval may reduce the recall of categorical memories in depression). Likewise, a gist-based predisposition in older adults (e.g., Koutstaal et al, 2003;Tun et al, 1998) may, across time, make more specific retrieval ever more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in clinical depression, a sustained orientation toward the retrieval of general or categoric memories (Williams & Dritschel, 1992) may make it increasingly difficult to retrieve specific episodes or details, further compounding the impairments in problem solving that overly general memory retrieval may yield (e.g., Raes et al, 2005;Sidley, Whitaker, Calam, & Wells, 1997;see, especially, Watkins, Teasdale, & Williams, 2000, for evidence that alterations of cognitive state at the time of memory retrieval may reduce the recall of categorical memories in depression). Likewise, a gist-based predisposition in older adults (e.g., Koutstaal et al, 2003;Tun et al, 1998) may, across time, make more specific retrieval ever more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Two groups of researchers have replicated Williams and Broadbent's (1986) findings of overgeneral recall in patients who attempted suicide (Evans et al, 1992;Sidley et al, 1997). Moreover, McNally, Lasko, Macklin, and Pitman (1995) reported patients with PTSD have similar difficulties in retrieving specific memories.…”
mentioning
confidence: 95%
“…In several studies, overgeneral retrieval has proved to be related to poor problem solving (Evans, Williams, O'Loughlin, & Howells, 1992;Goddard et al, 1996;Sidley, Whitaker, Calam, & Wells, 1997), and it may be a predictor for the course of depression (Brittlebank, Scott, Williams, & Ferrier, 1993; but see Brewin et al, 1999). Mackinger et al (2000) provide further evidence for the persistent nature of overgeneral retrieval style.…”
mentioning
confidence: 99%
“…However, there are good reasons to believe that a lack of specificity is not mood-dependent but rather reflects a stable trait (e.g., Williams, 1996). To begin with, a number of studies failed to find significant correlations between mood questionnaire scores and overgeneral recall (Kuyken & Brewin, 1995;Merckelbach, Muris & Horselenberg, 1996;Sidley, Whitaker, Calam & Wells, 1997;Williams & Dritschel, 1988). Furthermore, Williams and Dritschel (1988) found that recovered overdose patients were comparable to current overdose patients in terms of their autobiographical memory performance.…”
Section: Introductionmentioning
confidence: 99%